Environmental enrichment is associated with favorable memory-related functional brain activity patterns in older adults - Hass, Simon; Liebscher, Maxie; Richter, Anni; Fliessbach, Klaus; Laske, Christoph; Sodenkamp, Sebastian; Peters, Oliver; Hellmann-Regen, Julian; Ersözlü, Ersin; Priller, Josef; Spruth, Eike Jakob; Altenstein, Slawek; et al. (Frontiers in Aging Neuroscience, 2024)
BackgroundIn humans, environmental enrichment (EE), as measured by the engagement in a variety of leisure activities, has been associated with larger hippocampal structure and better memory function. The present cross-sectional study assessed whether EE during early life (13–30 years) and midlife (30–65 years) is associated with better preserved memory-related brain activity patterns in older age.MethodsIn total, 372 cognitively unimpaired older adults (aged ≥60 years old) of the DZNE-Longitudinal Study on Cognitive Impairment and Dementia (DELCODE; DRKS00007966) were investigated. EE was operationalized using items of the Lifetime of Experiences Questionnaire (LEQ), which measures the self-reported participation in a variety of leisure activities in early life and midlife. The preservation of memory-related functional brain activity was assessed using single-value scores, which relate older adults’ brain activity patterns in the temporo-parieto-occipital memory network to those of young adults during visual memory encoding (FADE and SAME scores).ResultsEE during early life and midlife was significantly associated with higher SAME scores during novelty processing (n = 372, β = 0.13, p = 0.011). Thus, older participants with higher EE showed greater similarity of functional brain activity patterns during novelty processing with young adults. This positive association was observed most strongly in participants with subjective cognitive decline (SCD, n = 199, β = 0.20, p = 0.006).ConclusionMore frequent participation in a variety of leisure activities in early life and midlife is associated with more successful aging of functional brain activity patterns in the memory network of older adults, including participants at increased risk for dementia. Longitudinal studies are needed to clarify whether higher EE during life could help preserve memory network function in later life.